2016
DOI: 10.12659/msm.897714
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Intima-Media Thickness as the Cardiometabolic Risk Indicator in Patients with Nonfunctional Adrenal Mass and Metabolic Syndrome Screening

Abstract: BackgroundOur purpose was to show the association of adrenal incidentaloma and metabolic syndrome in consideration of the studies and to detect the increase in the carotid intima-media thickness which is regarded as the precessor of atherosclerosis.Material/MethodsEighty-one patients who were diagnosed with adrenal mass were included in the study. Hormonal evaluation, insulin rezistance measurement with the HOMA-IR and 1-mg DST were performed of all patients. The patients were classified as follows: mass size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 27 publications
(30 reference statements)
2
14
0
Order By: Relevance
“…Some studies have also demonstrated higher frequencies of metabolic syndrome components in NFAI patients . In this context, our results are in line with previous reports, which have demonstrated increased frequency of glucose and lipid disturbances and arterial hypertension.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Some studies have also demonstrated higher frequencies of metabolic syndrome components in NFAI patients . In this context, our results are in line with previous reports, which have demonstrated increased frequency of glucose and lipid disturbances and arterial hypertension.…”
Section: Discussionsupporting
confidence: 93%
“…Despite the growing number of studies evidencing a higher frequency of these isolated components of metabolic syndrome in the NFAI population, [18][19][20][21][22][23] it has been assumed this is the first clinical study to evaluate and classify patients with NFAI by different Some studies have also demonstrated higher frequencies of metabolic syndrome components in NFAI patients. [18][19][20][21][22][23] In this context, our results are in line with previous reports, which have demonstrated increased frequency of glucose and lipid disturbances and arterial hypertension. In a multicenter urban Brazilian population study, the prediabetes rate in the 60-to 69-year-old group was 11.2%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrospective analysis unexpectedly revealed that also asymptomatic patients with adrenal adenomas and low-grade autonomous cortisol secretion suffer from a higher rate of CV events and mortality than patients with normal HPA axis suppression (5,6,7). Despite these epidemiological associations, only two small studies investigated morphological and functional changes to the CV system in patients with mild hypercortisolism (8,9). In particular, they did not investigate whether CV changes correlated to cortisol levels.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it can measure the thickness of ventricular wall and carotid intima-media, which are risk factors of cardiovascular diseases. And we know that heart failure is a state of most cardiovascular diseases [30, 31]. So in this research, we selected the transthoracic echocardiography for evaluations of cardiac functions.…”
Section: Discussionmentioning
confidence: 99%